Arbovírus dos gêneros Flavivirus e Alphavirus em culicídeos capturados em Cuiabá, Mato Grosso - Serra, Otacília Pereira (2015)
Arbovirus are transmitted by hematophagous arthropods, posing a public health issue in tropical areas. The aim of this study was to investigate the diversity of culicidae and their frequency of infection by arboviruses from Alphavirus and Flavivirus genus in Cuiabá, MT. To achieve that, culicids were captured with Nasci aspirators and hand net between January and April 2013 in three locations of 200 censitary sectors randomly defined. The specimens were identified using the Forattini dichotomy key, allocated in pools (1-20 mosquitoes), according to sex, species, day and place of capture, and stored at -80˚C. Female pools were subjected to total RNA and DNA extraction and to multiplex semi-nested-RT-PCR for five alphaviruses and 11 flaviviruses and Nested-PCR for Culex (Cx.) quinquefasciatus identification. The pools positive for SLEV, DENV-1, -4 and MAYV were subjected to single RT-PCR and nucleotide sequencing. MAYVpositive pools were inoculated in Vero cells and subjected to RT-PCR for the E1 envelope gene of alphaviruses. Pools positive for flaviviruses were inoculated in C6/36 cells. The minimum infection rate (MIR) was calculated. 11,090 mosquitoes were captured, 4,556 females belonging to 14 species, comprising 610 pools, 171 pools of Aedes (Ae.) aegypti specimens; 1 Ae. albopictus; 1 Aedes sp.; 5 Cx. bidens/interfor; 1 Cx. spinosus; 403 Cx. quinquefasciatus; 1 Galindomyia sp.; 6 Limatus sp.; 2 Mansonia wilsoni; 5 Psorophora sp.; 1 Ps. ciliata; 11 Ps. varipes/albigenu; 1 Sabethes chloropterus e 1 Uranotaenia sp. Among them, 1/171 (MIR=0.92) Ae. aegypti pool was positive for DENV-1 and 1/403 (MIR=0.3) Cx. quinquefasciatus for SLEV genotype V-A. For MAYV, 12/403 (MIR=3.5) Cx. quinquefasciatus, 4/171 (MIR=3.67) Ae. aegypti were positive, five of them were also infected by DENV-4. A DNA product with 1.3 kb obtained from three pools positive for MAYV with the protocol for the envelope gene resulted in unspecific nucleotide sequences. MAYV was isolated from two pools, both containing two non-engorged females of Ae. aegypti (#958) and Cx. quinquefasciatus (#489). DENV-4 was detected in 58/171 (MIR=53.35) Ae. aegytpi, 105/403 (MIR=30,65) Cx. quinquefasciatus, 2/5 (MIR=400) Psorophora sp., 2/11 (MIR=142.85) Ps. varipes/albigenu, 1/1 (MIR= 1000) Sabethes chloropterus, 2/5 (MIR=285.7) Cx. bidens/interfor and 1/1 (MIR=1000) Aedes sp. DENV-4 was isolated from two pools containing three (#329) and 16 (#806) non-engorged females of Cx. quinquefasciatus. The SLEV, MAYV and the four DENV serotypes were identified in patients suspected of harboring dengue infection in Cuiabá in previous studies of the Virology Laboratory. Experimentally, Culex and Aedes spp. are competent vectors for MAYV. The identification of the virus in nonengorged females suggests these species may be involved in the urban cycle of MAYV in Cuiabá. Among the DENV serotypes, only DENV-1 and DENV-4 were identified in culicids captured in the city. DENV-4 has been responsible for major outbreaks in MT since 2012. The identification of DENV-4 in several mosquito species might be resultant either from natural infection or hematophagy in humans, since several of these pools presented engorged females. Cuiabá presents a favorable ecosystem for the occurrence of arboviruses and vector proliferation. Studies involving entomological and virological surveillance are important to estimate the epidemiological situation of arboviruses in the state.